Persepsi Pengasuh Lansia: Comfort Food dan Penyediaan Makanan di Panti Wreda - Rayanti, Rosiana Eva; Aitonam, Defeni Ester; de Fretes, Fiane (JURNAL RISET GIZI, 2024)
Background: The number of older adults who have poor nutritional status is still often found in nursing homes in Salatiga City. Lack of appetite is the leading cause of poor nutritional status. Even though the nursing home has provided a healthy food menu for each older person, comfort food can be used to increase appetite so that the nutritional status of the elderly improves. This research aims to describe perceptions of comfort food to elderly caregivers in providing food at the Salatiga Nursing Home. The research method is qualitative with a descriptive approach. The criteria for participants are caregivers or caretakers of older adults aged 30-60 years who work in nursing homes to provide food and can still communicate. The research participants were ten caregivers or administrators of the three nursing homes in Salatiga City, Central Java nursing homes. The research results were five themes: first, food menu management, selection of food menus for the elderly, preparation of menu lists in nursing homes made by the caregivers, and asking the elderly about their food preferences. Both elderly eating habits and nutritional status, older adults have the habit of not finishing food if it does not suit their taste. Third, caregivers often feel sad and disappointed when older people do not finish their food. The fourth is the meaning of comfort food, which is everyone's favorite food from childhood. Fifth, comfort food is needed to manage food in nursing homes. Conclusions show that comfort food is understood as a term for favorite foods or favorite foods for caregivers in nursing homes but has not yet been used as an approach in the nutritional management of the elderly.